An Overview on Black Hairy Tongue Treated Constitutionally Through Homoeopathy–A Case Report (Homoeopathy for All, 2023)
Black hairy tongue is a benign self limiting disorder characterized by  hypertrophy of the filiform papillae of  the tongue. In this condition a brown ish-black discoloration of the papillae  occurs.The etiology is still unclear  but the condition is associated with  numerous predisposing conditions.  Homoeopathic medicine prescribed  after proper casetaking and repertor ization has shown effectiveness in  treating blackhairy tongue. A 45-year old woman came with a complaint of  blackish discoloration on tongue. A  detailed case history was taken and  after proper repertorization, the con stitutional medicine was prescribed  along with repeated follow-ups were  taken at an interval of 15 days. The  follow-ups of the patient showed re markable improvement in her condi tion.
Keywords: Black hairy tongue; Homoeopathy; Repertorization; Constitutional